Association between Sudden Sensorineural Hearing Loss and Preexisting Thyroid Diseases: A Nationwide Case-Control Study in Taiwan - Tsai, Yao-Te (Int J Environ Res Public Health, 2020)
Background: Little evidence is available about the risk of sudden sensorineural hearing loss (SSNHL) in patients with thyroid diseases. We assessed whether a diagnosis of thyroid disease, particularly hyperthyroidism or hypothyroidism, is associated with SSNHL risk in an Asian population. Material and Methods: This case-control study was conducted with population-based data from Taiwan’s National Health Insurance Research Database from January 2000 to December 2013. The case group comprised 3331 adult patients with newly diagnosed SSNHL, and four controls without SSNHL for each case matched by sex, age, monthly income, and urbanization level of residence. Underlying Thyroid diseases were retrospectively evaluated in the case and control groups. Multivariate logistic regression analyses were used to explore relations between thyroid diseases and SSNHL. Results: Of the 3331 cases, 5.7% had preexisting thyroid diseases, whereas only 4.0% of the 13,324 controls had the same condition. After adjustment for sex, age, monthly income, urbanization level of residence, history of hypertension, diabetes mellitus, chronic otitis media, and hyperlipidemia, associations were identified between a history of either hypothyroidism (adjusted odds ratio [AOR], 1.54; 95% CI, 1.02–2.32; p = 0.042) or hyperthyroidism (AOR, 1.41; 95% CI, 1.07–1.85; p = 0.015) and an elevated risk of SSNHL. In subgroup analysis, the correlation between hypothyroidism and increased SSNHL risk remained significant only for patients aged over 50 years (AOR, 1.61; 95% CI, 1.01–2.57; p = 0.045), and that between hyperthyroidism and SSNHL was significant only for female patients (AOR, 1.48; 95% CI, 1.09–2.01; p = 0.012). Treatment for hypothyroidism and hyperthyroidism did not alter the association in subgroup analyses. Conclusion: Preexisting hypothyroidism and hyperthyroidism appear associated with SSNHL susceptibility in Taiwan. Physicians should be wary of this elevated risk of SSNHL among patients with previously diagnosed thyroid dysfunction, especially women and patients aged more than 50 years.